Alpine ski injuries and their prevention - Koehle, M. S.; Lloyd-Smith, R.; Taunton, J. E. (Sports Medicine, 2002)
Alpine skiing is a popular sport with significant risk of injury. Since the 1970s, injury rates have dropped from approximately 5 to 8 per 1000 skier-days to about 2 to 3 per 1000 skier-days. The nature of the injuries has also been transformed over the same period. Lower leg injuries are becoming less common while the incidence of knee sprains and upper extremity injuries is becoming more common. Much of this change can be attributed to advancements in binding technology, which effectively reduces lower leg injury, but does not adequately address the issue of knee sprains. Along with design, binding adjustment and maintenance are important preventative factors. Poorly adjusted bindings have been correlated with increased injury rates. Upper extremity injuries constitute approximately one-third of skiing injuries, with ulnar collateral ligament sprains and shoulder injuries being the most common. Strategies to prevent these include proper poling technique and avoidance of non-detachable ski pole retention devices. Spinal injuries in skiers have been traditionally much less common than in snowboarders, but this disparity is likely to diminish with the recent trend of incorporating snowboarding moves into skiing. Strategies to help reduce these injuries include promoting the development of terrain parks and focussing on proper technique during such moves. Head injuries have been increasing in incidence over recent decades and account for more than half of skiing-related deaths. The issue of ski helmets remains controversial while evidence for their efficacy remains under debate. There is no evidence to demonstrate that traditional ski instruction reduces injury frequency. More specific programmes focussed on injury prevention techniques are effective. The question of pre-season conditioning to prevent injuries needs further research to demonstrate efficacy.